MANAGEMENT FISIOTERAPI DENGAN DIATERMY DAN TERAPI LATIHAN PADA KASUS LOW BACK PAIN ET. CAUSA ISCHIALGIA: A CASE REPORT - Fauziyyah, Ifah Nur; Wahyuni, Wahyuni; Sukatwa, Sukatwa (Journal of Innovation Research and Knowledge, 2024)
Introduction: Low back pain (LBP) is a common musculoskeletal disorder. LBP patients usually experience weakness in the back muscles compared to people who do not experience back pain. In addition, decreased propeoception can cause problems for spinal stability which can lead to recurring pain. Ischialgia is a symptom of back pain caused by compression of the sciatic nerve. Method: This research method uses a case report carried out at RSJD Dr RM Soedjarwadi Klaten on female patients Mrs. S is 61 years old. The patient's physiotherapy diagnosis was Low Back Pain et. causa Ischialgia. The patient has carried out a physiotherapy program for 1 week twice with a total of 4 training sessions. Results: The patient complained of low back pain, radiating to the right leg, the pain increased when moved, and interfered with daily activities. Seeing the patient's condition, we carried out physiotherapy interventions 2 times a week, a total of 4 meetings in this study. Evaluations are carried out 4 times at each meeting. Conclusion: Based on case report studies, the Diathermy method and exercise therapy have been proven to be effective, especially for reducing lower back pain. In functional activities there is a decrease in pain and an increase in muscle strength. The conclusion from the evaluation results of the therapy provided showed improvement